Genotoxicidade, citotoxicidade, compostos fenólicos e viabilidade polínica de Psidium cattleianum Sabine (Myrtaceae) - Hister, Carmine Aparecida Lenz (2015)
Psidium cattleianum Sabine, also known as strawberry guava, is a Brazilian native species whose fruits are valued for a high level of vitamin C, which are consumed in natura. Besides, it is also a species used for medicinal purposes. The use of plants as a therapeutic resource is a widely spread practice in popular medicine worldwide, although there have been few studies about their chemical composition as well as their potential risks to human health. Besides, the germplasm characterization of a species, as the pollen viability determination for instance, is important in maintaining a database that may be useful for future research. Considering that some plants cause adverse effects, the purpose of the present study was to analyze the antiproliferative and genotoxic effect of strawberry guava juice and strawberry guava leaf aqueous extracts by Allium cepa test system. This study also aimed at analyzing strawberry guava pollen grains through different colorimetric techniques so as to assess their viability. Fruits from three accessions were used for preparing juice at the concentration of 125 g.L-1, and dried leaves from four accessions were used for preparing aqueous extracts at the concentrations of 15 g.L-1 and 75 g.L-1. Distilled water was used as negative control, whereas glyphosate served as positive control. Inhibition of cell division as well as the occurrence of chromosomal abnormalities in the meristematic cells of Allium cepa roots were also analyzed. In order to identify the phenolic compounds, juice and aqueous extract samples were analyzed by high performance liquid chromatography (HPLC). The pollen viability of twenty accessions was determined by two colorimetric methods. The statistical analysis was carried out using Chi-square and Scott-Knott tests (p < 0,05). The analysis of genotoxicity showed that the strawberry guava juice induced cell proliferation and chromosomal abnormalities, besides inhibiting the formation of the mitotic spindle. The extracts prepared with leaves from four strawberry guava accessions caused a decrease in cell proliferation, however, only the extracts prepared with leaves collected in Cerro Largo (CL) induced chromosomal alterations. The following phenolic compounds were identified in the composition of the strawberry guava juice and the leaf aqueous extracts: gallic acid, catechin, chrologenic acid, caffeic acid, ellagic acid, epicatechin, rutin, quercitrin, isoquercitrin, quercetin and kaempferol. The pollen viability determined through 2% acetic orcein was higher than 97,9%, and between 43% and 97% when determined through Alexander s stain. One concluded that the strawberry guava juice has proliferative, genotoxic and anti-mitotic action upon Allium cepa. Moreover, the leaf aqueous extracts produce an antiproliferative effect, whereas the accession collected in Cerro Largo is genotoxic, which may be valid to other types of eukaryotic cells. The most predominant phenolic compounds identified in the strawberry guava juice were epicatechin (two accessions) and isoquercitrin (one accession). Quercitrin was the most predominant compound in the leaf aqueous extracts from one accession, and quercetin was the most predominant one in the remaining accessions. One also concluded that the Alexander s stain was more accurate in regard to the actual pollen viability mainly due to its two stains (green malachite and fuchsine).